Ambiguous Beliefs on Damages and Civil Liability Theories - Gérard Mondello (Fondazione Eni Enrico Mattei (FEEM), 2013)
This paper analyzes the meaning of comparing the economic performance of strict liability and negligence rule in a unilateral standard accident model under Knightian uncertainty. It focuses on the cost expectation of major harm on which the injurers form beliefs. It shows first that, when the Court agrees with the regulator, whatever the liability regime, the first best level of care is never reached but under both regimes the tortfeasors define the same level of care. Second, when, judge and regulator disagree, it is impossible to discriminate among liability standards because the issue depends on the injurer's optimism degree.
Keywords: K0; K32; Q01; Q58; 330; Strict Liability; Negligence Rule; Ambiguity Theory; Uncertainty; Accident Model